Knowledge level of mothers of toddlers diagnosed with acute respiratory infection at Dinoyo Community Health Center, Malang City - Rusdiana, Husna; Atmadani, Rizka Novia (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2022)
Acute Respiratory Infection (ARI) is an attack by viruses and bacteria in the upper and lower respiratory tract. The cause of the increase in the number of ARI sufferers can also be influenced by the level of parents' own knowledge of information about ARI. This study aims to analyze the level of knowledge of mothers of toddlers diagnosed with ARI. This research uses quantitative research methods which are observational research using cross-sectional studies by giving questionnaires to respondents. The sample in this study were 65 mothers of toddlers who were diagnosed with ARI at the Dinoyo Community Health Center, Malang City. The results showed that the knowledge level was found to be 89.2% good, 10.85% adequate, and 0% poor. Based on the results of the chi-square test analysis, it shows that in this study, mother's age, domicile, employment, health insurance, family income, and age of toddlers have a significance value of more than 0.05 so that it can be said that they do not have a relationship with the level of knowledge of mothers of toddlers diagnosed with ARI. There is no relationship between sociodemographic factors and the level of knowledge of mothers of toddlers.